Prediksi Sebaran Partikulat Insinerator Rsud Arifin Achmad Menggunakan Screen View - Hardyan, Rici; Sasmita, Aryo; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hospitals as health facilities that are curative and rehabilitative should be free of pollutants such as particulate matter. One cause of the particulate matter in the hospital is incineration. Hospital incinerators that burn trash in hazardous / infectious, so it is necessary to determine the level of distribution of the particulates produced by burning incinerator. This research is a descriptive study using dispersion method gauss with Screen View program. Parameters that are seen medical waste generation, particulate concentrations, wind direction and wind speed, and distance distribution of particulates. The data obtained are presented in the form of graphs and tables. The highest particulate distribution on the wind direction is north east with the concentration of 2.32 Î¼g / m3 at a distance of 100 m from the incineratorat a distance of 100 m from the incinerator emissions rate 0.00957 g/s, 0.38 stack inside diameter and 9 m stack high.Key word: incinerator, particulate, screen view, wind direction, wind speed.